ANTECEDENTS OF INTEREST IN PURCHASING ELECTRIC MOTORCYCLES IN MEDAN - Christopher Christopher; Purnama Yanti Purba; Lulu Nitama Harianja; Elfina Okto Posmaida Damanik; Enda Noviyanti Simorangkir (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
This study aims to analyze the influence of technological innovation, environmental awareness, and price on the purchase intention of electric motorcycles in Medan City. The research employs a quantitative approach with a causal research design. The population consists of residents of Medan City who use electric motorcycles, and the sample was determined using random sampling, resulting in one hundred respondents. Data were collected through observation and questionnaires. The data analysis includes validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), and simultaneous tests (F-tests) using IBM SPSS Statistics version 23. The results show that partially technological innovation has a positive and significant effect on purchase intention for electric motorcycles, environmental awareness also positively influences consumers’ intention to buy, and price is identified as a significant and positive factor that affects consumers’ purchasing decisions. Simultaneously, these three variables strongly influence the increase in purchase intention for electric motorcycles in Medan City. These findings indicate that technological innovation, environmental awareness, and price are essential components in developing strategies to expand the electric vehicle market in Indonesia.